COMPARATIVE EVALUATION OF THE MAIN PARAMETERS OF RACING DISTANCES OF THE LARGEST INTERNATIONAL AND ALL-RUSSIAN COMPETITIONS IN MODERN ROAD CYCLING - Kubeev, A.V.; Oganesyan, A.A.; Savenkova, E.A.; Matina, V.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to conduct a comparative assessment of the difficulties of the racing distances of the largest international and Russian road cycling competitions. Methods and structure of the study. The distance profiles of all stages of the Grand Tour series for the period 2018-2021 were collected and analyzed (220 stages in total), as well as the Russian championships in group races for men over the same period. Also, the methods used in cycling and other sports for assessing the difficulty of competitive distances were studied and their characteristic features were identified. Results and conclusions. A publicly available method based on open data for assessing the difficulty of distances is proposed, recommendations are given for modernizing the structure and content of the calendar of Russian road cycling and sports training programs for young athletes. The obtained results of the study give specialists the necessary grounds for modernizing the structure and content of the calendar of all-Russian road cycling competitions, and also set clear guidelines in the development of the strategy and tactics of training programs for Russian cyclists in the context of the system of long-term sports training.